Perceptions of Crime Prevention Through Environmental Design (CPTED) at Australian Railway Stations - Cozens, Paul; van der Linde, T. (2015)
Personal safety and security are essential criteria for measuring the quality of public transport, and research has consistently demonstrated that crime and fear of crime affect levels of patronage. Although authorities throughout the world are implementing Crime Prevention Through Environmental Design (CPTED), research and practice commonly focus on the elements of surveillance, territoriality, and controlling access. Few studies have investigated the CPTED concepts of “image management” or “geographical juxtaposition” (the surrounding environment). This research compares and contrasts the perceptions of rail users and security experts in relation to two railway stations in Perth, Western Australia. One station was designed in accordance with CPTED principles, and one was not. Interestingly, the findings indicate that the rail users perceived the station that was not designed using CPTED to be marginally safer and to exhibit slightly higher levels of CPTED qualities. This exploratory investigation suggests that the effectiveness of CPTED is mediated by the local environment surrounding each station and its associated image.